The health system cost of post-abortion care in Uganda - Michael Vlassoff; Frederick Mugisha; Aparna Sundaram; Akinrinola Bankole; Susheela Singh; Leo Amanya; Charles Kiggundu; Florence Mirembe (2012)
This article presents estimates based on the research conducted in 2010 of the cost to the Ugandan health system of providing post-abortion care (PAC), filling a gap in knowledge of the cost of unsafe abortion. Thirty-nine public and private health facilities were sampled representing three levels of health care, and data were collected on drugs, supplies, material, personnel time and out-of-pocket expenses. In addition, direct non-medical costs in the form of overhead and capital costs were also measured. Our results show that the average annual PAC cost per client, across five types of abortion complications, was $131. The total cost of PAC nationally, including direct non-medical costs, was estimated to be $13.9 million per year. Satisfying all demand for PAC would raise the national cost to $20.8 million per year. This shows that PAC consumes a substantial portion of the total expenditure in reproductive health in Uganda. Investing more resources in family planning programmes to prevent unwanted and mistimed pregnancies would help reduce health systems costs.